Treatment of hemangioma of the spleen by preoperative partial splenic embolization plus laparoscopic partial splenectomy: A case report. Issue 17 (April 2018) - Zheng, Lu; Deng, Changlin; Li, Jing; Wang, Liang; You, Nan; Wu, Ke; Wang, Weiwei
Abstract: Rationale: Complete loss of splenic function increases infection and cardiovascular disease risks, so there is growing emphasis on spleen-preserving treatments, such as laproscopic partial splenectomy (LPS). However, LPS carries higher risk for hemorrhage. Sequential splenic embolization can obliterate the perilesional vascular bed while preserving flow through healthy tissue, substantially reducing risk of uncontrolled hemorrhage during LPS. Preoperative partial splenic embolization (PSE) may soften the spleen and reduce its size, which enhances space exposure for laparoscopic operation. Furthermore, immediate LPS guaranties these effects of PSE and prevents abscess, non-traumatic splenic rupture, post-embolization syndrome, and other complications. In light of these advantages, we conducted combined PSE and LPS for a case of hemangioma. Patient concerns: The patient presented with left abdominal discomfort of >1 year. Diagnoses: Ultrasound examination at the outpatient clinic identified a space-occupying lesion in the spleen. Contrast-enhanced computed tomography scan of the upper abdomen revealed a hypodense lesion, approximately 33 × 21 mm in size, located in the upper pole of the spleen, suggesting possible hemangioma. Interventions: The patient was treated by preoperative PSE followed by LPS. Outcomes: Treatment resulted in only mild intraoperative hemorrhage, fast postoperative recovery, and no recurrence during follow-up. And the postoperative histopathology confirmed splenic cavernous hemangioma. Lessions: Preoperative PSE combined with LPS is an effective therapy for elective patients that minimizes intraoperative hemorrhage during laparoscopic surgery, reduces surgical risk, and enhances surgical safety.